Method for efficiently leaching vanadium titano-magnetite concentrate through low-concentration acid
By using the composite force field in the low-concentration acid-efficient leaching method of vanadium titanium magnetite concentrate, the problem of low separation and recovery of vanadium titanium magnetite is solved, and efficient leaching of titanium, iron, vanadium and the preparation of high-quality artificial rutile are achieved, providing high-quality raw materials for titanium dioxide production.
Patent Information
- Application Number
- CN202410611161.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the separation recovery rate of vanadium titanium magnetite is low, the separation is incomplete, and the process is long.
The high-efficiency leaching method of low-concentration acid is adopted to perform a leaching reaction between vanadium titanium magnetite concentrate and hydrochloric acid solution in a reactor with a composite force field, and the dissolution activity of the mineral is improved by using the magnetic field and stirring, and high-quality artificial rutile is obtained through alkaline leaching.
It has achieved efficient leaching of titanium, iron, vanadium and other elements under low concentration acid conditions, with the total recovery rate of titanium reaching more than 92%, and the leaching rate of vanadium and iron reaching more than 75% and more than 85% respectively, to obtain high-quality artificial rutile, providing high-quality raw materials for the production of titanium dioxide in chloride.
Smart Images

Figure CN119753321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy and specifically relates to a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid. Background Art
[0002] Vanadium-titanium magnetite is an important vanadium and titanium resource in my country. It is a complex mineral resource with vanadium, titanium and iron coexisting. It is mainly distributed in Panzhihua, Sichuan, Chaoyang, Liaoning, Chengde, Hebei and other regions in my country. The efficient and comprehensive recovery of metal resources such as vanadium, titanium and iron is a difficult problem in the industry. The vanadium-titanium magnetite concentrate in Panzhihua area is currently mainly processed through blast furnace smelting process. Although it can effectively realize the recovery of vanadium and iron, most of the titanium enters the blast furnace slag during the blast furnace ironmaking process. Almost all the titanium and about 30% of the vanadium in the vanadium-titanium magnetite concentrate enter the blast furnace slag and cannot be effectively utilized. The vanadium-titanium magnetite in western Liaoning has the characteristics of high vanadium and titanium and low iron. The iron grade of the concentrate obtained through ore dressing is low, and it is difficult to develop and utilize it using the traditional blast furnace-converter process. There is currently no effective treatment process.
[0003] In order to efficiently utilize complex multi-metal co-existing resources such as vanadium-titanium magnetite, the existing processes are all based on step-by-step extraction and recovery, which has problems such as low recovery rate, incomplete separation, and long process. Summary of the invention
[0004] The purpose of the present invention is to provide a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, which is used to solve one of the following technical problems: the separation recovery rate of vanadium-titanium magnetite in the prior art is low, the separation is incomplete, and the process is long.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] On the one hand, the present invention provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, the method comprising the following steps:
[0007] Step 1: Grind and screen the vanadium-titanium magnetite concentrate;
[0008] Step 2: Fully mix the vanadium-titanium magnetite concentrate with the hydrochloric acid solution, and place it in a reactor with a composite force field to carry out a leaching reaction; the composite force field includes a magnetic field and a stirring action;
[0009] Step 3: After the leaching reaction is completed, the reaction material is filtered to obtain a leaching solution containing titanium slag and vanadium-containing iron;
[0010] Step 4: alkaline leaching is performed on the titanium slag obtained in step 3 using an alkaline solution, and the filter cake obtained after filtration is high-quality artificial rutile.
[0011] Furthermore, in step 1, the main components of the vanadium-titanium magnetite concentrate include titanium-containing magnetite and ilmenite, which mainly contain iron, titanium and vanadium elements.
[0012] Furthermore, in step 1, the particle size range of the vanadium-titanium magnetite concentrate obtained after screening is: more than 90% under the 200-mesh sieve.
[0013] Furthermore, in step 2, the concentration of the hydrochloric acid solution is 13% to 18%.
[0014] Furthermore, in step 2, the ratio of the hydrochloric acid solution to the vanadium-titanium magnetite concentrate is 5 mL: 1 g to 15 mL: 1 g.
[0015] Furthermore, in step 2, the temperature of the leaching reaction is 110-170°C.
[0016] Furthermore, in step 2, during the leaching reaction, the magnetic field strength is controlled to be 0.01-2T.
[0017] Furthermore, in step 2, during the leaching reaction, the stirring speed is controlled to be 200 to 800 r / min.
[0018] Furthermore, in step 4, the alkaline solution can be a mixed solution of one or more of NaOH, KOH, and NH4OH.
[0019] Furthermore, in step 4, the temperature of alkaline leaching is controlled to be 70-95°C.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1) In the method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid provided by the present invention, a composite force field is added to change the crystal structure of magnetic ilmenite and magnetite in the vanadium-titanium magnetite concentrate, and the vacancy defects in the lattice and the change of atomic arrangement enhance its dissolution activity, change the leaching reaction mechanism, and realize efficient leaching of elements such as titanium, iron, and vanadium under low-concentration acid conditions. The instability of titanium ions after dissolution in a low-concentration acid environment is utilized to realize the leaching of titanium and simultaneous hydrolysis and precipitation, so as to achieve efficient separation of vanadium, iron and titanium. In addition, the magnetization of the magnetic field on the leachate can improve the hydrolysis process of titanium in the leachate, realize efficient hydrolysis of titanium, and obtain high-quality artificial rutile products by alkaline leaching and quality improvement, providing high-quality raw materials for the production of titanium dioxide by the chloride process.
[0022] 2) The method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid provided by the present invention achieves efficient leaching of elements such as titanium, iron, and vanadium under low-concentration acid conditions by precisely controlling process parameters such as magnetic field intensity, stirring speed, temperature, and acidity. The method has high efficiency and good leaching effect. The grade of artificial rutile obtained by the method of the present invention is more than 82%, for example, 82.7% to 95%; the total recovery rate of titanium is more than 92%, for example, 92.4% to 98%; the leaching rate of vanadium reaches more than 75%, for example, 75.8% to 96%; the leaching rate of iron reaches more than 85%, for example, 85.9% to 98%. The method of the present invention is suitable for large-scale application.
[0023] Other features and advantages of the present invention will be described in the following embodiments, and some of them can be obtained from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are only for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. The same reference symbols denote the same contents throughout the accompanying drawings.
[0025] Figure 1 The process flow chart of the method of the present invention is shown in FIG. DETAILED DESCRIPTION
[0026] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0027] The present invention provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, the method comprising the following steps:
[0028] Step 1: Grinding and sieving the vanadium-titanium magnetite concentrate to obtain vanadium-titanium magnetite concentrate with a certain particle size range;
[0029] Step 2: fully mix the vanadium-titanium magnetite concentrate with the hydrochloric acid solution, put it into a reactor with a composite force field, and carry out a leaching reaction at a certain temperature; the composite force field action includes a magnetic field action and a stirring action; specifically, the composite force field action includes a magnetic field force, a centrifugal force and a shear force;
[0030] Step 3: After the leaching reaction is completed, the reaction material is filtered to obtain a leaching solution containing titanium slag and vanadium-containing iron;
[0031] Step 4: alkaline leaching is performed on the titanium slag obtained in step 3 using an alkaline solution, and the filter cake obtained after filtration is high-quality artificial rutile.
[0032] The method of the present invention utilizes the magnetism of the vanadium-titanium magnetite concentrate itself and adopts a magnetic field to achieve the dissolution of the vanadium-titanium magnetite concentrate under low acid concentration conditions, shorten the reaction time required for acid dissolution, and improve production efficiency; during the leaching process, the titanium component is dissolved and then hydrolyzed and precipitated synchronously, and high-quality artificial rutile can be obtained by alkali leaching and quality improvement.
[0033] Specifically, in step 1, the vanadium-titanium magnetite concentrate is a beneficiation concentrate from Chaoyang area in western Liaoning. The main components of the vanadium-titanium magnetite concentrate include titanomagnetite and ilmenite, and mainly contain valuable metal elements such as iron, titanium, and vanadium. The mass percentages of some components in the vanadium-titanium magnetite concentrate are as follows: TFe43.5%, TiO2 9.3%, and V 0.24%. The vanadium-titanium magnetite concentrate is magnetic.
[0034] Specifically, in step 1, the particle size range of the vanadium-titanium magnetite concentrate obtained after screening is: more than 90% under the 200-mesh sieve.
[0035] Specifically, in step 2, if the concentration of the hydrochloric acid solution is too low, the leaching reaction is incomplete; if the concentration of the hydrochloric acid solution is too high, it is easy to cause incomplete hydrolysis and precipitation of the dissolved titanium in the leaching process, corrode the reaction container, and subsequently produce a large amount of high-concentration waste acid solution, which has a high production cost; therefore, the concentration of the hydrochloric acid solution is controlled to be 13% to 18%. For example, the concentration of the hydrochloric acid solution is 14%, 15%, 16%, and 17%.
[0036] Specifically, in step 2, considering that when the slurry concentration is low, the processing volume is limited and the acid reaction is incomplete; when the slurry concentration is high, it is difficult to mix the reaction materials and the reaction efficiency is low; when the reaction temperature is low, the reaction rate is slow and the production efficiency is low. When the reaction temperature is too high, the pressure resistance of the reactor is high; when the reaction time is short, the reaction is incomplete, and excessively extending the reaction time reduces the production efficiency; therefore, the ratio of hydrochloric acid solution to vanadium titanium magnetite concentrate is controlled to be (5mL:1g)~(15mL:1g); the temperature range of the leaching reaction is 110~170℃, and the leaching reaction time is 1~3h; illustratively, the ratio of hydrochloric acid solution to vanadium titanium magnetite concentrate is 7mL:1g, 10mL:1g, 13mL:1g; the leaching reaction temperature is 120℃, 130℃, 140℃, 150℃, 160℃; the reaction time is 1.5h, 2h, 2.5h.
[0037] Specifically, in step 2, the reactor with a composite force field refers to a leaching reactor having an induction coil or a permanent magnet to generate a magnetic field, and a stirring device to generate centrifugal force and shear force, including but not limited to a high-pressure reactor.
[0038] Specifically, in step 2, based on the magnetic characteristics of the vanadium-titanium magnetite concentrate of the present invention, the present invention adds a magnetic field during the reaction process, so that the crystal structure of the magnetic ilmenite and magnetite in the vanadium-titanium magnetite concentrate changes, and the vacancy defects in the lattice and the change of the atomic arrangement enhance their dissolution activity, thereby changing the leaching reaction mechanism and achieving efficient leaching of elements such as titanium, iron, and vanadium under low-concentration acid conditions; the magnetic field also has a magnetizing effect on the aqueous solution, and the radius of the hydrated ion state of the metal element can be reduced during the magnetization process, and the degree of hydration can be reduced, thereby improving the hydrolysis nucleation ability of the metal ion, and titanium in the solution is more likely to nucleate and crystallize out from the solution; the larger the magnetic field, the more obvious the magnetization effect. Considering that when the magnetic field intensity is low, the strengthening effect on the acid leaching process of vanadium-titanium magnetite concentrate is weak; when the magnetic field intensity is high, the cost of magnetic field equipment increases exponentially, and the increase in leaching strengthening effect is not significant; therefore, the magnetic field intensity is controlled to be 0.01~2T, and the type of magnetic field is one of pulsed magnetic field or constant magnetic field or a combination of two; exemplarily, the magnetic field intensity is 0.05T, 0.1T, 0.5T, 1T, 1.5T, 2T.
[0039] Specifically, in step 2, the magnetic field is generated by electromagnetic or permanent magnet.
[0040] Specifically, in step 2, stirring is performed during the leaching process. Considering that when the stirring speed is slow, the mixing of solid and liquid in the slurry and the diffusion of reactants are insufficient, the reaction efficiency is low; when the stirring speed is fast, the slurry is easily swirled, and the solid particles and liquid reactants rotate at the same speed, which does not have a stirring effect; therefore, the stirring speed is controlled to be 200-800r / min, and exemplary, the stirring speed is 300r / min, 400r / min, 500r / min, 600r / min, and 700r / min.
[0041] Specifically, in step 2, the stirring is performed by swirl stirring or impeller stirring. For example, a mechanical stirring device may be used for stirring.
[0042] It should be noted that the premise for efficient leaching of vanadium, titanium and iron in vanadium-titanium magnetite concentrate is that the acid concentration is high enough; but the hydrolysis and precipitation of the titanium component after dissolution requires the solution to be under low acid concentration conditions. Temperature and acid concentration are the main factors affecting the speed of the leaching process, and are also the main factors affecting the hydrolysis of titanium, and the effects on leaching and hydrolysis are opposite. Therefore, with the help of the effect of the magnetic field on the crystal structure of magnetic minerals, the leaching activity of magnetic minerals is improved, and efficient leaching of concentrates at lower acidity is achieved; during the leaching process, part of the acid is consumed, reducing the acid concentration, and then with the help of the magnetization of the magnetic field on the aqueous solution, the hydrolysis of the titanium component after dissolution is strengthened. During the leaching process, the acid will be consumed, and at the same time, the hydrolysis of the titanium component after dissolution will produce acid, which increases the acid concentration; therefore, the acid concentration during the leaching process is related to the initial acid concentration added, the degree of leaching reaction and the hydrolysis rate of the titanium component. In the present invention, by accurately controlling the process parameters of each step, the concentration of the acid used is low, the temperature is low, the safety is good, the leaching time is short, and the efficiency is high.
[0043] Considering that the interaction between the pulsed magnetic field and the mineral is intermittent, a resonance-like effect can be achieved by adjusting the magnetic field pulse frequency, resulting in more mineral lattice defects and improving leaching activity. Therefore, the magnetic field in step 2 can be a pulsed magnetic field.
[0044] It should be noted that if the intensity of the pulsed magnetic field is too small, the enhanced leaching effect will not be obvious. If the intensity of the magnetic field is too large, the leaching effect will be limited, but the equipment manufacturing cost will increase exponentially. If the pulse time interval is too small or too large, it is difficult to enhance the leaching process of magnetic minerals, and a certain degree of matching with the magnetic substances in the minerals is required. Therefore, taking comprehensive considerations, the pulse interval is controlled to be 1 to 10 seconds and the magnetic field intensity is 0.01 to 2T.
[0045] Specifically, in the above step 2, the magnetic field strength is 0.01~<0.5T, and the pulse interval is 1~3s; the magnetic field strength is 0.5~<1T, and the pulse interval is 3~7s (for example, 3~5s); the magnetic field strength is 1~2T, and the pulse interval is 4~10s (for example, 4~7s).
[0046] Specifically, in step 3, filtration is achieved by, including but not limited to, a filter press and a plate and frame filter, and after filtration, the filter cake is washed with industrial water until it is neutral.
[0047] Specifically, in step 3, the vanadium and iron in the leaching solution containing vanadium and iron can be recovered step by step by conventional solvent extraction and spray pyrolysis.
[0048] Specifically, in step 4, the alkaline solution can be one or a mixed solution of NaOH, KOH, and NH4OH.
[0049] Specifically, in step 4, the alkaline solution is preferably NaOH or NH4OH in consideration of cost.
[0050] Specifically, in step 4, considering that the alkali concentration is low, the impurity removal effect is not obvious, and the alkali concentration is too high, the production cost is high; the increase in solution temperature helps to improve the reaction efficiency of the alkali leaching process, but the high temperature does not significantly improve the reaction efficiency but increases energy consumption; the reaction time is short, the impurity removal is not thorough, the rutile product grade is low, and the reaction time is too long, then the production cycle is long and the production efficiency is low. Therefore, the alkali concentration is controlled to be 1.0-2.0 mol / L, and the reaction is carried out for 1-2 hours under normal pressure and solution temperature of 70-95°C; for example, the alkali concentration is 1.3 mol / L, 1.5 mol / L, the solution temperature is 75°C, 80°C, 85°C, and the reaction time is 1.2h, 1.5h, 1.8h.
[0051] Specifically, the method of the present invention obtains an artificial rutile grade of more than 82%, for example, 82.7% to 96%; the total titanium recovery rate is more than 90%, for example, 90% to 98%; the vanadium leaching rate reaches more than 75%, for example, 75.8% to 97%; the iron leaching rate reaches more than 85%, for example, 85.9% to 98%.
[0052] It should be noted that, based on the magnetic field and the magnetizing force between atoms and electrons, the Lorentz force and other effects, the magnetic field has a certain influence on the thermodynamics and kinetics of the chemical reaction between substances, but this influence requires the magnetic field intensity to be large enough, reaching more than 10T, before it can have a significant effect on the chemical reaction, and when the magnetic field intensity is weak, the influence of the magnetic field in this aspect is weak and can be ignored. However, in the present invention, for magnetic minerals, the magnetic field can change the vibration and orientation of the magnetic ions in the magnetic minerals, so that vacancy defects are produced in the mineral crystal structure, and it has higher reactivity. Therefore, based on the magnetic characteristics of the vanadium-titanium magnetite concentrate of the present invention, the present invention adds a magnetic field device outside the reactor, so that the ilmenite and magnetite crystal structures with magnetism in the vanadium-titanium magnetite concentrate change, and the vacancy defects in the lattice and the transformation of the atomic arrangement enhance its dissolution activity, change the leaching reaction mechanism, realize the efficient leaching of elements such as titanium, iron, and vanadium under low acid concentration conditions, and utilize the instability of titanium ions after dissolution under low acid concentration environment, realize the leaching of titanium and synchronous hydrolysis precipitation, and achieve efficient separation of vanadium, iron and titanium. In addition, the magnetization effect of the magnetic field on the leachate can improve the hydrolysis process of titanium in the leachate and achieve efficient hydrolysis of titanium. High-quality artificial rutile products can be obtained through alkaline leaching and quality improvement, providing high-quality raw materials for the production of titanium dioxide by the chloride process.
[0053] Example 1
[0054] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, comprising the following steps:
[0055] The vanadium-titanium magnetite concentrate is ground and sieved to obtain vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with a 13% hydrochloric acid solution, the ratio of the hydrochloric acid solution to the concentrate is (5mL: 1g), and after being fully mixed, it is placed in a reactor with a composite force field that can generate a magnetic field strength of 0.01T, and reacted at 110°C and a stirring speed of 200r / min for 1 hour; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leaching solution; a 1.0mol / L NaOH solution is used to leach the titanium slag at 70°C for 1 hour, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leaching solution can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 75.8% and 85.9% respectively; the TiO2 content in the titanium slag was 54.8wt.%; the grade of artificial rutile obtained after alkali leaching was 82.7%, and the total titanium recovery rate was 92.4%.
[0056] Example 2
[0057] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, comprising the following steps:
[0058] The vanadium-titanium magnetite concentrate is ground and sieved to obtain vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with a 15% hydrochloric acid solution, the ratio of the hydrochloric acid solution to the concentrate is (10mL: 1g), and after being fully mixed, it is placed in a reactor with a composite force field that can generate a magnetic field strength of 0.1T, and reacted at 130°C and a stirring speed of 500r / min for 2 hours; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leaching solution; a 2.0mol / L NaOH solution is used to leach the titanium slag at 95°C for 2 hours, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leaching solution can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 84.1% and 89.2% respectively; the TiO2 content in the titanium slag was 65.8%; the grade of artificial rutile obtained after alkali leaching was 91.7%, and the total titanium recovery rate was 95.8%.
[0059] Example 3
[0060] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, comprising the following steps:
[0061] The vanadium-titanium magnetite concentrate is ground and sieved to obtain vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with 18% hydrochloric acid solution, the ratio of hydrochloric acid solution to concentrate is (15mL: 1g), and after fully mixing, it is placed in a reactor capable of generating a magnetic field strength of 1T with a composite force field effect, and reacted for 3 hours at 170°C and a stirring speed of 800r / min; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leaching solution; a 2.0mol / L NaOH solution is used to leach the titanium slag at 95°C for 2 hours, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leaching solution can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 90.1% and 92.4% respectively; the TiO2 content in the titanium slag was 74.2%; the grade of artificial rutile obtained after alkali leaching was 93.6%, and the total titanium recovery rate was 94.8%.
[0062] Example 4
[0063] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, comprising the following steps:
[0064] The vanadium-titanium magnetite concentrate is ground and sieved to obtain vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with a 15% hydrochloric acid solution, the ratio of the hydrochloric acid solution to the concentrate is (15mL: 1g), and after being fully mixed, it is placed in a reactor capable of generating a magnetic field strength of 2T with a composite force field effect, and reacted at 150°C and a stirring speed of 500r / min for 1 hour; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leaching solution; a 2.0mol / L NaOH solution is used to leach the titanium slag at 95°C for 2 hours, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leaching solution can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 95.1% and 97.4% respectively; the TiO2 content in the titanium slag was 76.4%; the grade of artificial rutile obtained after alkali leaching was 94.8%, and the total titanium recovery rate was 97.2%.
[0065] In summary, the method of the above embodiment adds a magnetic field generating device to the outside of the reactor, and changes the arrangement of vacancy defects and magnetic units in the mineral particles through the action of the magnetic field, so that the vanadium-titanium magnetite concentrate has higher reactivity, and can achieve efficient dissolution of components such as titanium, iron, and vanadium, and hydrolysis and precipitation of the titanium component after dissolution, thereby preparing high-quality artificial rutile. In addition, by comparing the embodiments, the increase in magnetic field strength within a certain range can effectively reduce the acid concentration, reaction temperature, shorten the reaction time, improve the reaction efficiency, and obtain titanium-containing slag and artificial rutile with higher grade; in order to obtain better leaching effect and artificial rutile quality, it is necessary to couple and control the magnetic field strength with temperature, acid concentration and other conditions.
[0066] Example 5
[0067] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, and the steps are basically the same as those in Example 3, except that:
[0068] The magnetic field is a pulsed magnetic field, the pulse interval is 3s, and the magnetic field strength is 1T. During the leaching process, the leaching rates of vanadium and iron are 96.8% and 97.2% respectively; the TiO2 content in the titanium slag is 75.8%; the grade of artificial rutile obtained after alkali leaching is 94.5%. The total recovery rate of titanium is 95.7%.
[0069] Example 6
[0070] This embodiment provides a method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, and the steps are basically the same as those in Example 3, except that:
[0071] The magnetic field type is a pulsed magnetic field, and the results under different magnetic field strengths and pulse intervals are shown in Table 1. It can be seen that when the magnetic field is a pulsed type, the leaching effect is better than that of a constant magnetic field type under the same conditions, and by adjusting the magnetic field strength and pulse interval, the leaching has a better optimization effect.
[0072] Table 1 Leaching of vanadium-titanium magnetite and rutile grade under different magnetic field strengths and pulse intervals
[0073]
[0074] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor effects as comparative examples.
[0075] Comparative Example 1
[0076] This comparative example provides a method for leaching vanadium-titanium magnetite concentrate. Compared with Example 4, the method of this comparative example has most of the same conditions, and the reaction is carried out under the condition of no magnetic field. The specific steps are as follows:
[0077] The vanadium-titanium magnetite concentrate is ground and sieved to obtain a vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with a 15% hydrochloric acid solution, the ratio of the hydrochloric acid solution to the concentrate is (15mL: 1g), and after being fully mixed, it is placed in a reactor with only a stirring device, and reacted at 150°C and a stirring speed of 500r / min for 1 hour; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leachate; a 2.0mol / L NaOH solution is used to leach the titanium slag at 95°C for 2 hours, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leachate can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 46.8% and 53.1% respectively; the TiO2 content in the titanium slag was 25.2%; the TiO2 content in the filter cake obtained after alkali leaching was 30.5%, and the total titanium recovery rate was 97.2%.
[0078] By comparison, it was found that under the condition of no magnetic field, the leaching effect of vanadium-titanium magnetite is poor. Since the acid leaching slag contains a large amount of unreacted ilmenite / magnetite, the TiO2 content in the titanium slag is low. Alkaline leaching cannot dissolve the unreacted ilmenite / magnetite and cannot obtain high-grade titanium-containing materials. Since titanium will eventually enter the slag regardless of whether leaching occurs or not, there will be no obvious difference in the total titanium recovery rate, and it is not the main reference basis.
[0079] Comparative Example 2
[0080] This comparative example provides a method for leaching vanadium-titanium magnetite concentrate. Compared with Example 3, the method of this comparative example has most of the same conditions, the difference is the concentration of hydrochloric acid during the acid leaching process, and the specific steps are as follows:
[0081] The vanadium-titanium magnetite concentrate is ground and sieved to obtain vanadium-titanium magnetite concentrate with a 200-mesh sieve accounting for 90%; the vanadium-titanium magnetite concentrate is fully mixed with a 24% hydrochloric acid solution, and the ratio of the hydrochloric acid solution to the concentrate is (15mL: 1g). After fully mixing, it is placed in a reactor capable of generating a magnetic field strength of 1T with a composite force field effect, and reacted for 3 hours at 170°C and a stirring speed of 800r / min; after the leaching reaction is completed, the reaction material is filtered through a filter press to obtain a titanium slag and a vanadium-containing iron leaching solution; a 2.0mol / L NaOH solution is used to leach the titanium slag at 95°C for 2 hours, and after the reaction is completed, the filter is filtered and the filter cake is washed to neutrality to obtain high-grade artificial rutile. The vanadium and iron in the vanadium-containing iron leaching solution can be recovered step by step by conventional solvent extraction and spray pyrolysis. During the leaching process, the leaching rates of vanadium and iron were 95.4% and 97.2% respectively; the TiO2 content in the titanium slag was 76.3%; the grade of artificial rutile obtained after alkali leaching was 94.8%, and the total titanium recovery rate was 70.9%.
[0082] By comparison, it was found that when the acid concentration was high, the leaching rate of ferrovanadium was high, and the TiO2 content in titanium slag and artificial rutile was high, but the total recovery rate of titanium was low; the reason is that the magnetic field can enhance the leaching effect of vanadium-titanium magnetite, and a better dissolution effect can be achieved in a lower concentration of acid solution. If the acid concentration is high, the hydrolysis and precipitation of the titanium component after dissolution will be incomplete, which will eventually lead to a low titanium recovery rate. Therefore, without adding a magnetic field, the acid concentration that can ensure the complete hydrolysis of titanium cannot completely leach the vanadium-titanium magnetite; under the condition of a magnetic field, the leaching process cannot use an acid solution with too high a concentration. It is necessary to reasonably arrange and adjust the magnetic field strength and acid concentration conditions to achieve efficient dissolution of vanadium-titanium magnetite and hydrolysis and precipitation of the titanium component after dissolution.
[0083] Comparative Example 3
[0084] This comparative example provides a method for leaching vanadium-titanium magnetite concentrate. Compared with Example 3, the method of this comparative example has most of the same conditions, the difference being that high-concentration acid and leaching are carried out in the absence of a magnetic field during the leaching process. The results are shown in Table 2. By comparison, it was found that under conditions without a magnetic field, the leaching effect was worse than under conditions with a magnetic field and the total recovery rate of titanium was lower. The reason is that the magnetic field can not only enhance the leaching, but also promote the hydrolysis and precipitation of the titanium component after dissolution, thereby increasing its recovery rate. When the acid concentration is 30%, the leaching effect remains basically unchanged, which is equivalent to the effect in Example 3, but the total recovery rate of titanium is lower than that in Example 3. The reason is that when the acid concentration is high, it is not conducive to the hydrolysis of the titanium component after dissolution, thereby reducing its recovery rate.
[0085] Table 2 Leaching and artificial rutile grade results under high concentration acid and no magnetic field conditions
[0086] Acid concentration / % Iron leaching rate / % Vanadium leaching rate / % Rutile grade / % Total recovery rate of titanium / % 24 91.1 89.8 92.4 85.6 30 92.0 91.4 92.7 76.5
[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for efficiently leaching vanadium-titanium magnetite concentrate with low-concentration acid, characterized in that: The method comprises the following steps: Step 1: Grind and screen the vanadium-titanium magnetite concentrate; Step 2: Fully mix the vanadium-titanium magnetite concentrate with the hydrochloric acid solution, and place it in a reactor with a composite force field to carry out a leaching reaction; the composite force field includes a magnetic field and a stirring action; Step 3: After the leaching reaction is completed, the reaction material is filtered to obtain a leaching solution containing titanium slag and vanadium-containing iron; Step 4: alkaline leaching is performed on the titanium slag obtained in step 3 using an alkaline solution, and the filter cake obtained after filtration is high-quality artificial rutile.
2. The method according to claim 1, characterized in that In step 1, the main components of the vanadium-titanium magnetite concentrate include titanium-containing magnetite and ilmenite, which mainly contain iron, titanium and vanadium elements.
3. The method according to claim 1, characterized in that In the step 1, the particle size range of the vanadium-titanium magnetite concentrate obtained after screening is: more than 90% of the particles are below the 200-mesh sieve.
4. The method according to claim 1, characterized in that: In step 2, the concentration of the hydrochloric acid solution is 13% to 18%.
5. The method according to claim 1, characterized in that In the step 2, the ratio of the hydrochloric acid solution to the vanadium-titanium magnetite concentrate is 5 mL: 1 g to 15 mL: 1 g.
6. The method according to claim 1, characterized in that In the step 2, the temperature of the leaching reaction is 110-170°C.
7. The method according to claim 1, characterized in that In the step 2, during the leaching reaction, the magnetic field strength is controlled to be 0.01-2T.
8. The method according to claim 1, characterized in that: In the step 2, during the leaching reaction, the stirring speed is controlled to be 200 to 800 r / min.
9. The method according to claim 1, characterized in that: In step 4, the alkaline solution can be one or a mixed solution of NaOH, KOH, and NH4OH.
10. The method according to any one of claims 1 to 9, characterized in that: In step 4, the temperature of alkaline leaching is controlled to be 70-95°C.